2022
DOI: 10.3390/genes13010129
|View full text |Cite
|
Sign up to set email alerts
|

Ancient DNA Methods Improve Forensic DNA Profiling of Korean War and World War II Unknowns

Abstract: The integration of massively parallel sequencing (MPS) technology into forensic casework has been of particular benefit to the identification of unknown military service members. However, highly degraded or chemically treated skeletal remains often fail to provide usable DNA profiles, even with sensitive mitochondrial (mt) DNA capture and MPS methods. In parallel, the ancient DNA field has developed workflows specifically for degraded DNA, resulting in the successful recovery of nuclear DNA and mtDNA from skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Techniques for identification of human remains continue to improve particularly with the capabilities of NGS and hybridization capture [ 595 ] and ancient DNA extraction protocols [ 596 , 597 ]. Studies have reported variation in skeletal DNA preservation [ 598 ] and retrospectively considered success rates with compromised human remains [ 599 ].…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…Techniques for identification of human remains continue to improve particularly with the capabilities of NGS and hybridization capture [ 595 ] and ancient DNA extraction protocols [ 596 , 597 ]. Studies have reported variation in skeletal DNA preservation [ 598 ] and retrospectively considered success rates with compromised human remains [ 599 ].…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…However, the feasibility of introducing ancient DNA methods into forensic methodology has recently been published. Authors have shown that implementing such methods improves forensic DNA profiling and they argue that it can increase the success rate for identifying historical remains [56,108].…”
Section: Where Paleogenetic and Forensic Sciences Convergementioning
confidence: 99%
“…The remains under the purview of KWIP originate from a 70-year-old conflict and are subject to a wide array of taphonomic conditions; therefore, the nDNA typically utilized in individual identification (i.e., short tandem repeats) is frequently too degraded for a complete, or even partial, profile (Zavala et al, 2022). Thus, mtDNA has become the primary modality of genetic analysis, aided by nDNA where possible, for the identification of Korean War losses.…”
Section: Box 2 Sanger and Next-generation Sequencingmentioning
confidence: 99%